2015
DOI: 10.1261/rna.052084.115
|View full text |Cite
|
Sign up to set email alerts
|

In vivo analysis of trypanosome mitochondrial RNA function by artificial site-specific RNA endonuclease-mediated knockdown

Abstract: Trypanosomes possess a unique mitochondrial genome called the kinetoplast DNA (kDNA). Many kDNA genes encode premRNAs that must undergo guide RNA-directed editing. In addition, alternative mRNA editing gives rise to diverse mRNAs and several kDNA genes encode open reading frames of unknown function. To better understand the mechanism of RNA editing and the function of mitochondrial RNAs in trypanosomes, we have developed a reverse genetic approach using artificial sitespecific RNA endonucleases (ASREs) to dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…If the dual-coding ARFs give BF trypanosomes a selective growth advantage similar to that observed by the COIII alternative protein AEP1, then the number of “essential” gRNA genes would increase greatly. Currently, only AEP1, A6 and RPS12 mitochondrial genes have been experimentally shown to be essential [12, 70-71]. In addition, the presence of alternative editing and dual-coding genes would complement the protection provided by gene fragmentation by also shielding the genes from deleterious point mutations within critical ETC genes.…”
Section: Discussionmentioning
confidence: 99%
“…If the dual-coding ARFs give BF trypanosomes a selective growth advantage similar to that observed by the COIII alternative protein AEP1, then the number of “essential” gRNA genes would increase greatly. Currently, only AEP1, A6 and RPS12 mitochondrial genes have been experimentally shown to be essential [12, 70-71]. In addition, the presence of alternative editing and dual-coding genes would complement the protection provided by gene fragmentation by also shielding the genes from deleterious point mutations within critical ETC genes.…”
Section: Discussionmentioning
confidence: 99%
“…The full coverage of COIII was also not surprising, as COIII was shown to be fully edited and equally abundant in both stages [ 17 ]. However, we expected to see complete coverage of ATPase 6 and RPS12 as both of these transcripts have been shown to be essential in both life cycle stages [ 3 , 44 , 45 , 50 ]. For ATPase 6, we did identify a total of 29 gRNA populations that do cover all of the editing sites.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, northern blot analysis of total RNA showed that cytoplasmic RNAs containing perfect or nearperfect eight-nucleotide sequences were not cleaved, which strongly suggests that A6-ASRE only cleaved mtRNA targets, and is thus highly specific. Measurements of mitochondrial membrane potential (ΔΨm) also confirmed that mitochondrial activity was reduced upon A6-ASRE induction, causing a 100fold increase in sensitivity to oligomycin, an ATP synthase inhibitor [112].…”
Section: (C) Targeted Mtrna Nucleasesmentioning
confidence: 77%
“…The authors attributed this to inadequate protein import or low transfection efficiency, while stable cell lines producing mitoASREs enabled a reduction of 70% in MT-ND5 mRNA [110]. Further work by Choudhury and co-workers expanded the PUF-PIN ASRE system to target and knock-down specific mtRNAs of Trypanosoma brucei [112]. Trypanosomes are parasitic protists with a host life cycle that rotates between insect vectors, such as the tsetse fly, and mammals, specifically cattle, where they cause African sleeping sickness [113].…”
Section: (C) Targeted Mtrna Nucleasesmentioning
confidence: 99%
See 1 more Smart Citation